2016
DOI: 10.1620/tjem.240.7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Ligation for Patent Ductus Arteriosus in Extremely Premature Infants: Strategy to Reduce their Risk of Neurodevelopmental Impairment

Abstract: Surgical ligation for patent ductus arteriosus (PDA) in extremely low birth weight infants (ELBWIs) has been shown a possible association with neurodevelopmental impairment (NDI) because of its invasiveness. However, we have undergone surgical ligation for ELBWIs immediately after cyclooxygenase inhibitor failed to close a hemodynamically significant PDA (hsPDA) to maintain proper systemic circulation. We aimed to determine the effect of surgical ligation for hsPDA on NDI in ELBWIs. In enrolled 71 ELBWIs, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“… 2 Patent DA (PDA) increases the mortality risk of premature infants. 3 , 4 Since the mid-1970s, COX inhibitors targeting smooth muscle cell (SMC) contraction represent the only pharmacological treatment for PDA, but >30% of these patients are still resistant to COX inhibitor therapy. 2 COX inhibitors have serious side effects on premature infants such as renal failure and neonatal necrotizing enterocolitis.…”
mentioning
confidence: 99%
“… 2 Patent DA (PDA) increases the mortality risk of premature infants. 3 , 4 Since the mid-1970s, COX inhibitors targeting smooth muscle cell (SMC) contraction represent the only pharmacological treatment for PDA, but >30% of these patients are still resistant to COX inhibitor therapy. 2 COX inhibitors have serious side effects on premature infants such as renal failure and neonatal necrotizing enterocolitis.…”
mentioning
confidence: 99%
“…Many studies have been conducted to examine the mortality rate of this method. For example, Satoko et al (2016) reported a mortality rate of 9.9% and neurological disorder prevalence of 21.1% in this method (5), which depicts a declining trend compared to the previous studies (13% and 44%, respectively) (6). In our study, the 30-day mortality rate of patients was zero, though investigation with a larger sample size is required to confirm the results.…”
Section: Discussionmentioning
confidence: 67%
“…The authors suggested two possible explanations for these findings to include shorter time to exposure to both PDA duration and cumulative pharmacological side effects. In another study by Ito et al, 22 the authors suggested immediate SL of PDA in ELBW infants if medical treatment fails to minimize the duration of exposure to a hemodynamically significant PDA and to prevent future NDI. Vida et al 23 also reported the benefits of early PDA SL in premature infants <32 weeks of GA after two failed ibuprofen cycles (median age at PDA closure 8 days in early group vs. 14 days in late group; p < 0.0001), especially in reducing the risk of BPD and acute renal failure, highlighting that prolonging medical treatment to avoid SL can be associated with increased morbidity and hospital length of stay.…”
Section: Discussionmentioning
confidence: 99%